Kejadian Low Back Pain pada Mekanik Bagian UPT Mekanisasi di Dinas Tanaman Pangan dan Hortikultura Provinsi Riau - Kursiah Warti Ningsih; Dwi Sapta; Rudi Fernando (Jurnal Kesehatan Komunitas, 2016)
Low Back Pain (LBP) is pain felt in the lower back area, may be a local pain (inflammation), or radicular pain or both. Low back pain is a disease that most experienced workers, where the incidence of lower back pain knows no differences in age, sex, occupation, social status, or level of education / knowledge, can all be affected. More than 70% of people in his life ever experienced lower back pain, with an average peak incidence 35-55 years old. This research was conducted at the Department of Food Crops and Horticulture Riau province in July 2014. The study design was cross-sectional with a number of respondents as many as 32 workers. The data collection is done with low back pain in the form of body mapping instrument checklist, and instrument variables collection of knowledge, work period and age of workers with the questionnaire as a tool in data collection. Analysis of the data using linear regression. These results indicate that there is a significant relationship between the worker's age and years of service with the incidence of low back pain. These results indicate that an increase of 1 point the worker's age there will be an increase of 0,084 points low back pain on workers and an increase of 1 point tenure there will be an increase of 0.097 points low back pain in workers. Suggested to the Department of Food Crops and Horticulture Riau province to hold a morning exercise every week to strengthen bone mass, decrease chronic joint pain in the waist, back and knee recalling the events of low back pain is related to age and work period.